Fermi-surface topology of rare-earth dihydrides - Koitzsch, Christian; Hayoz, J.; Bovet, M; Clerc, Florian; Despont, Laurent; Ambrosch-Draxl, Claudia; Aebi, Philipp (My University, 2004)
We report high-resolution angle-resolved photoemission experiments on epitaxial thin films of different rare-earth (RE) dihydrides (RE=Gd,La) and of YH2 and ScH2 . It is found through ab initio calculations and confirmed by Fermi surface mapping that the electronic structure becomes very similar upon hydrogenation, rendering the studied dihydrides isoelectronic. We propose that the dihydride phase acts as a common precursor state for the formation of the insulating trihydride phase. For states with higher binding energies (which exhibit considerable H character) the agreement between calculation and measurement is less convincing. Independent of the difficulties to describe these hydrogen related states, we note in the comparison between experiment and calculation a very convincing description of the Fermi surface for the dihydrides. Therefore we trace the apparent inability of density, functional theory to describe the hygrogenation up to the trihydride phase to an insufficient description of hydrogen states in general and, in particular, involving octahedral sites.